C-C Bond formation catalyzed by natural gelatin and collagen proteins - Kuehbeck, Dennis; Dhar, Basab Bijayi; Schoen, Eva-Maria; Cativiela, Carlos; Gotor-Fernandez, Vicente; Diaz, David Diaz (Beilstein Journal of Organic Chemistry, 2013)
The activity of gelatin and collagen proteins towards C-C bond formation via Henry (nitroaldol) reaction between aldehydes and nitroalkanes is demonstrated for the first time. Among other variables, protein source, physical state and chemical modification influence product yield and kinetics, affording the nitroaldol products in both aqueous and organic media under mild conditions. Significantly, the scale-up of the process between 4-nitrobenzaldehyde and nitromethane is successfully achieved at 1 g scale and in good yield. A comparative kinetic study with other biocatalysts shows an increase of the first-order rate constant in the order chitosan < gelatin < bovine serum albumin (BSA) < collagen. The results of this study indicate that simple edible gelatin can promote C-C bond forming reactions under physiological conditions, which may have important implications from a metabolic perspective.
Keywords: biocatalysis; carbon-carbon bond formation; gelatin; Henry reaction; protein

Protein ligand complex guided approach for virtual screening - Karthikeyan, Muthukumarasamy; Pandit, Deepak; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
The target ligand association data is a rich source of information which is not exploited enough for drug design efforts in virtual screening. A java based open-source toolkit for Protein Ligand Network Extraction (J-ProLiNE) focused on protein-ligand complex analysis with several features integrated in a distributed computing network has been developed. Sequence alignment and similarity search components have been automated to yield local, global alignment scores along with similarity and distance scores. 10000 proteins with co-crystallized ligands from pdb and MOAD databases were extracted and analyzed for revealing relationships between targets, ligands and scaffolds. Through this analysis, we could generate a protein ligand network to identify the promiscuous and selective scaffolds for multiple classes of proteins targets. Using J-ProLiNE we created a 507 x 507 matrix of protein targets and native ligands belonging to six enzyme classes and analyzed the results to elucidate the protein-protein, protein-ligand and ligand-ligand interactions. In yet another application of the J-ProLiNE software, we were able to process kinase related information stored in US patents to construct disease-gene-ligand-scaffold networks. It is hoped that the studies presented here will enable target ligand knowledge based virtual screening for inhibitor design.
Keywords: Complexes; ligand; protein; scaffolds; sequences; similarity score; virtual screening

Interaction of polymers with amyloidogenic peptides - Abraham, Jancy Nixon; Nardin, Corinne (Polymer International, 2018)
With this review, the aim was to gather recent representative publications which describe the interaction of polymers with amyloidogenic peptides/proteins. When functional, these take part in for instance bacterial adhesion and biofilm formation. However, several of the peptides/proteins have been identified in various diseases. One of the current approaches to discover a cure against these relies on therapeutics which either prevent or accelerate peptide/protein aggregation and/or clear readily formed aggregates. Owing to the common interest of scientists from all disciplines to identify a cure against the diseases of public health concern, there are overwhelming numbers of publications dealing with these two approaches. Since amyloid aggregation could be regarded as a nucleated polymerization, which is an established mechanism of polymer self-assembly, we recently tackled the issue of amyloid aggregation using the theories and methods established in polymer science. In this review, we hence focus on gathering relevant and recent publications which describe the role of polymers in modulating the aggregation of amyloidogenic peptides/proteins. (c) 2017 Society of Chemical Industry
Keywords: amyloid; neurodegenerative diseases; Polymer; protein; Self-assembly

Opaque cell-specific proteome of Candida albicans ATCC 10231 - Abdulghani, Mazen; Telang, Saraswati; Desai, Manisha; Kadam, Shivdas; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Maurya, Radheshyam; Zore, Gajanan (Medical Mycology, 2023)
Candida albicans, a polymorphic opportunistic pathogen of humans, can exist in different morphological forms like yeast, hyphae, pseudohyphae, chlamydospores, and white and opaque cells. Proteomic analysis of opaque form of C. albicans ATCC 10231 is carried out in the present study using microflow liquid chromatography-tandem mass spectrometry and validated using expression analysis of selected genes using reverse transcription quantitative real-time PCR and mitochondrial membrane potential assay. This is the first report identifying opaque cell-specific proteins of C. albicans. A total of 188 proteins were significantly modulated under opaque form compared to white cells, of which 110 were upregulated, and 78 were downregulated. It was observed that oxidative phosphorylation (OxPhos) and oxidative stress are enhanced in C. albicans cells growing under opaque form as proteins involved in OxPhos (Atp1, Atp3, Atp16, Atp7, Cox6, Nuc2, Qcr7, and Sdh12) and oxidative stress response (Gcs1, Gtt11, Gpx2, Sod1, Ccp1, and Lys7) were significantly upregulated. The maximum upregulation of 23.16- and 13.93-fold is observed in the cases of Ccp1 and Nuc2, respectively. The downregulation of proteins, namely Als1, Csh1, Sap9, and Rho1, determining cell surface chemistry indicates modulation in cell wall integrity and reduced adhesion of opaque cells compared to white cells. This study is significant as it is the first draft of the proteomic profile of opaque cells that suggests enhanced OxPhos, oxidative stress, and modulation in cell surface chemistry indicating reduced adhesion and cell wall integrity, which could be associated with reduced virulence in opaque form. However, a deeper investigation is needed to explore it further. Lay Summary Opaque form is one of the least studied morphological forms of Candida albicans. To the best of our knowledge, this is the first report providing opaque cell-specific proteome. It suggests enhanced oxidative phosphorylation, oxidative stress, and modulation in cell surface chemistry, which could be associated with reduced virulence in opaque form.
Keywords: albicans; C; LC-MS; MS; opaque; Oxidative stress; OxPhos; protein